A novel fabrication of yttria-stabilized-zirconia dense electrolyte for solid oxide fuel cells by 3D printing technique - Wei, L.; Zhang, J.; Yu, F.; Zhang, W.; Meng, X.; Yang, N.; Liu, Shaomin (Elsevier Ltd, 2019)
Three-dimensional (3D) printing technique represents a revolutionary advancement in the manufacturing sector due to its unique capabilities to process the shape complexity. This work is focusing on dense 8 mol.% yttria-stabilized-zirconia (8YSZ) electrolyte fabrication via digital light processing (DLP)-stereolithography-based 3D printing technique. Multiple 8YSZ electrolyte green bodies are printed simultaneously in a batch using ceramic-resin suspension made of 30 vol% 8YSZ powder loading in a photo-curable resin. Together with an optimized debinding and sintering procedure, the 8YSZ green body changes into a dense electrolyte, and the density of the sintered electrolyte was measured as 99.96% by Archimedes’ water displacement method. The symmetric cell fabricated of silver-Ce0.8Gd0.2O1.9 (Ag-GDC) as cathode/anode and dense 8YSZ electrolyte printed by DLP-stereolithography delivers a high open circuit voltage of approximately 1.04 V and a peak power density up to 176 mW·cm-2 at 850 °C by using hydrogen as the fuel and air as the oxidant. The electrochemical performance of the symmetric cell Ag-GDC|YSZ|Ag-GDC with 8YSZ electrolyte fabricated via DLP-stereolithography is comparable to that of the same cell with 8YSZ electrolyte fabricated by conventional dry pressing method. This 3D printing technique provides a novel method to prepare dense electrolytes for solid oxide fuel cell (SOFC) with good performance, suggesting a potential application for one-step fabrication of complex structure SOFC stack.